ENHANCING THE PERFORMANCE OF SOLAR TOWER POWER PLANTS USING AN AUXILIARY HEAT SOURCE - Yazdi, Mohammad Hossein; A., Mahrooghi; O, Zarandi (Journal of Engineering & Technological Advances, 2024)
The solar tower power plant represents a cutting-edge solar thermal system designed to harness clean solar energy for electricity generation. Due to its abundant availability and cost-effectiveness, this technology has garnered significant interest recently. Solar power, as one of the most promising renewable energy sources, offers a sustainable alternative to fossil fuels, contributing to a reduction in greenhouse gas emissions and dependence on non-renewable energy resources. However, a major challenge lies in the plant’s low efficiency and its inability to generate electricity during nighttime, cloudy weather, or rainfall. To tackle this challenge, our approach involves designing a solar tower power plant that integrates an external heat source to complement solar energy and ensure uninterrupted electricity production. This integration not only enhances the reliability of the power supply but also maximizes the utilization of renewable energy resources. The collector, a crucial component of the solar tower power plant, accounts for a significant portion of both construction costs and energy loss. Improving the collector’s performance is therefore essential for enhancing the overall efficiency and economic viability of the plant. In this project, a novel collector design is proposed that not only heats the air under the collector through solar radiation but also utilizes an auxiliary heat source to further raise the air temperature. This increase in temperature accelerates air flow, which in turn enhances turbine rotation and consequently boosts electricity generation.